Kastolan Theory Error Analysis on Vocational School Students – A Case on Sequences and Series Topics - Nurhasanah, Alya Siti; Anita, Ika Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
The purpose of this study is to analyze the mistakes made by students while working on math problems in Sequence and series. The background to this study is that it is difficult to understand students during their studies, which leads to mistakes in solving the math problems of Sequence and series. The purpose of this study is to determine what mistakes are common in solving questions about Sequence and series. The subjects of this study were 10 students of eleventh grade at SMK Plus Darussurur, Cimahi City. The data collection method uses written essay questions with results obtained from the analysis of the level of error based on the Kastolan Theory.  Based on the results of the research and discussion, it was found that the level of student errors in working on sequence and series problems is as follows : 1) Conceptual errors with a percentage rate of 50% with the criterion of "High Enough" error rate; 2) Procedural Errors with a percentage rate of 32.1% with the criterion of "Low" error rate; 3) Technical errors with a percentage of 17.9% with the "Very Low" error rate criterion. From this, we can conclude that the common error in solving the Sequence and seriesproblem is a form of conceptual error. This means that the students' conceptual understanding of Sequence and series is still lacking. Because learning tends to focus on procedures without linking basic concepts, lack of visualization and real context, and limited abstract thinking skills and varied exercises.